Pelatihan Penguatan Asesment Formatif Sebagai Bagian Pengembangan Modul Ajar - Nurdinah Hanifah; Isrok’atun; Dadan Djuanda (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Compiling and formulating learning tools is one of the important tasks carried out by an educator. Curriculum development and change is a necessity, the independent curriculum is the latest curriculum to be implemented in 2022. In its implementation, significant differences arise related to the preparation of learning tools. This gives rise to problems in developing learning tools, including: difficulties in identifying CP, compiling TP (learning objectives from existing) CP (learning outcomes), formulating ATP (learning objective flow) from TP, and describing it in learning assessment. The implementation of this service activity uses the method online lectures, discussions and questions and answers. At each stage of implementation, the Direct Instruction strategy was used. The results of this activity show the teacher's ability to create modules, especially when developing assessments. This can be seen from the teaching modules that have been produced in the process and after service activities. From the results of the questionnaire given at the end of the activity, it appears that the direct benefits of the PkM activities carried out were 82.% in the Very Good category.